Effect of Mental Practice on Eye-Hand Coordination in the Healthy Girls between 20-25 Years Old - Mohammad Ja'afar Shater-; Shabnam Shahali; Rabe'eh Arian; Reza Salehi (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: People can to make mental relation between mental and motor procedures, without external motivation, who excited these procedures. This ability is named motor imagery. Mental practice is the acquisition of a physical skill through mental imagery. In the other word it is a cognitive rehearsal in the absence of actual performance of physical movements. This study was conducted for this aim: the effect of mental practice on eye hand coordination in the healthy girls between 20-25 years old. Materials & Methods: The study was a quasi experimental and applied research. Study's population was 45 girls between 20-25 years old. The tool for data collection was E-Link system from movement tracking laboratory in rehabilitation school. In this study we investigated eye hand coordination after mental and physical practice. Subjects randomly assigned. Physical practice group, applied practice in physical form for 10 sessions. Mental practice group, were imagine the stages of practice and the control group didn't do any practice. Results: Findings shows that the physical practice group had the most progress in eye hand coordination (P<0.05), we had seen progress in eye hand coordination in mental practice group but this progress was less than physical group (P